The effect of procedural injustice during emergency 911 calls: a factorial vignette-based study - Flippin, Michaela (Journal of experimental criminology, 2019)
This study tests the effects of procedurally unfair treatment by 911 dispatchers on behavioral intentions to cooperate with criminal justice professionals.